PENGARUH JUMLAH UANG BEREDAR (JUB), INFLASI, DAN SUKUK TERHADAP KAPITALISASI PASAR INDEKS SAHAM SYARIAH INDONESIA (ISSI) DENGAN NILAI TUKAR (KURS) SEBAGAI VARIABEL MODERASI - Aeni, Nor; Arinta, Yusvita Nena (Journal of Sharia Economics, 2025)
This study aims to examine the influence of money supply, inflation, and sukuk on the market capitalization of the Indonesia Sharia Stock Index (ISSI), with the exchange rate as a moderating variable. The research is grounded in the growing significance of the Islamic capital market amid macroeconomic fluctuations, particularly during the 2020–2024 period marked by the COVID-19 pandemic and global uncertainty. A quantitative approach is employed using monthly time series data, analyzed through multiple linear regression and Moderated Regression Analysis (MRA) with EViews 13 software. The results of the study show that: (1) the amount of money in circulation has a significant negative effect on the ISSI market capitalization (2) inflation has a significant positive effect on the ISSI market capitalization (3) sukuk does not have a significant effect on the ISSI market capitalization (4) the exchange rate has a significant negative effect on the ISSI market capitalization, (5) the exchange rate is able to significantly moderate the effect of the amount of money in circulation on the ISSI market capitalization, (6) the exchange rate is able to significantly moderate the effect of inflation on the ISSI market capitalization, (7) the exchange rate is not able to significantly moderate the effect of sukuk on the ISSI market capitalization.